GREEN SYNTHESIS, CHARACTERIZATION, ANTIMICROBIAL AND CYTOTOXIC EFFECTS OF SILVER NANOPARTICLES USING ORIGANUM HERACLEOTICUM L. LEAF EXTRACT - Rajendran, Ravikumar; Ganesan, Nithya; Balu, Satheesh Kumar; Alagar, Srinivasan; Thandavamoorthy, Premkumar; Thiruvengadam, Devaki (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)
Objectives: Silver nanoparticles (AgNPs) possess unique features among noble metal nanoparticles due to their wide range of applications in various field including medicine, environmental safety, etc. The present study relies on eco-friendly, cost effective method for the synthesis of AgNPs. Methods: AgNPs were rapidly synthesized from AgNO3 using aqueous leaf extract of O. heracleoticum L. as reducing as well as capping agent. Synthesized AgNPs were characterized with the help of FE-SEM, XRD, EDS and UVâ€“vis absorption spectroscopy. FE-SEM showed the spherical nature of nanoparticles with the size ranging from 30-40 nm. In addition, their antibacterial activities against standard bacterial pathogens were evaluated as per the standard disk diffusion method. Further, cytotoxicity potential of AgNPs were also determined using the MTT assay. Results: X-ray diffraction analysis showed that the nanoparticles formed in the present synthesis were crystalline in nature. FT-IR analysis showed the presence of possible biomolecules needed for reducing silver ions. Further, antibacterial activity of synthesized AgNPs showed effective inhibition against pathogenic microbes. In addition, these green synthesized nanoparticles were shown to exhibit potential cytotoxic effect on MCF-7 cell line in dose dependent manner. Conclusion: It has been demonstrated that O. heracleoticum L. plant extract could be used as a proficient green reducing agent for the synthesis of AgNPs. Further, these synthesized AgNPs were shown to exhibit effective antibacterial effect against pathogens and potential cytotoxic effect on MCF-7 cells. Â 